HEPATOSOMATIC INDEX (HSI) DAN DIAMETER HEPATOSIT MENCIT (Mus musculus L.) SETELAH PAPARAN EKSTRAK AIR BIJI PEPAYA (Carica papaya L.) - Perwitasari Wahyuningtyas; Agung Janika Sitasiwi; Siti Muflichatun Mardiati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2018)
Papaya seeds were one part of the papaya plants that can be used as a traditional medicine. The purpose of this study was to test the effect of papaya seed extract (Carica papaya L.) to Hepatosomatic Index (HSI) and hepatocytes diameter of mice (Mus musculus L.). This study was an experimental study use Completely Randomized Design (CRD) that divided into 5 treatment groups with 3 replications. P0 test material in the form of aquadest, P1, P2, P3 in the form of papaya seeds extract test with dose respectively 1.4; 3.5; And 7 mg / mL. Treatment were administered orally for 21 consecutive days. The Body weights of mice were measured every 7 days. After treatment were terminated, the body weights of mice were measured and then sacrificed by dislocation of the neck and the liver were taken by surgery. Furthermore, the liver weights were measured and made histological preparations with HE staining. The determination of HSI were obtained from liver weights and body weights. The measurement of hepatocytes diameter were done by using photomicrograph at each incision 3 field of view. Data were analyzed by Analysis of Variance (ANOVA) at 95% confidence level. The analysis result of HSI in the treatment group showed that there were no significant difference (p>0,05). The analisys of hepatocytes diameter of the treatment group showed significant difference (p<0.05). It could be concluded that exposure of papaya seeds extract for 21 days was a reversible effects so that the hepatocytes diameter size of mice increases but didn’t changed the HSI.Keywords: Carica papaya, HSI, hepatocytes diameter